Classification of some countable descendant-homogeneous digraphs - Amato,D; Evans,DM; Truss,JK (Discrete Mathematics, 2012)
For finite q, we classify the countable, descendant-homogeneous digraphs in which the descendant set of any vertex is a q-valent tree. We also give conditions on a rooted digraph Γ which allows us to construct a countable descendant-homogeneous digraph in which the descendant set of any vertex is isomorphic to Γ. © 2011 Elsevier B.V. All rights reserved.